Jawabanmu

2014-03-31T18:51:59+07:00
2014-03-31T18:58:13+07:00
Sec² α - sin² α sec² α = 1
 1      -  sin² α    1       1      - sin² α  = cos² α - sin² α cos² α
cos² α             cos² α    cos² α   cos² α        cos² α cos² α
                                                        =  cos² α ( 1 - sin² α )
                                                              cos² α cos² α
                                                        =    cos² α cos² α  = 1
                                                               cos² α cos² α